2016
DOI: 10.1183/13993003.01605-2016
|View full text |Cite
|
Sign up to set email alerts
|

The Global Asthma Network rationale and methods for Phase I global surveillance: prevalence, severity, management and risk factors

Abstract: The Global Asthma Network (GAN), established in 2012, followed the International Study of Asthma and Allergies in Childhood (ISAAC). ISAAC Phase One involved over 700 000 adolescents and children from 156 centres in 56 countries; it found marked worldwide variation in symptom prevalence of asthma, rhinitis and eczema that was not explained by the current understanding of these diseases; ISAAC Phase Three involved over 1 187 496 adolescents and children (237 centres in 98 countries). It found that asthma sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
136
0
10

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(162 citation statements)
references
References 21 publications
(19 reference statements)
0
136
0
10
Order By: Relevance
“…Some factors have been explored in ISAAC and GAN, such as changes in diet, time spent using screens (computers and video games), second-hand smoke, and the presence of pollutants. 10,20 In the present study, possible risk factors identified for WHEZEV and WHEZ12 were the presence of other allergic diseases (hay fever and eczema), early infections, smoking at home, and paracetamol use. These patterns have been described previously; for example, the evolution of allergic sensitization followed by atopic dermatitis, allergic rhinitis, and asthma have been demonstrated in several epidemiological studies.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Some factors have been explored in ISAAC and GAN, such as changes in diet, time spent using screens (computers and video games), second-hand smoke, and the presence of pollutants. 10,20 In the present study, possible risk factors identified for WHEZEV and WHEZ12 were the presence of other allergic diseases (hay fever and eczema), early infections, smoking at home, and paracetamol use. These patterns have been described previously; for example, the evolution of allergic sensitization followed by atopic dermatitis, allergic rhinitis, and asthma have been demonstrated in several epidemiological studies.…”
Section: Discussionmentioning
confidence: 56%
“…After providing informed consent, parents completed validated and standardized questionnaires given by GAN's global coordination for the younger group, and the older group completed the questionnaires by themselves. 10 Following the official GAN protocol, 10 the sample unit was the whole population of children aged 6-7 years or adolescents aged 13-14 years in a given school. The schools were within a certain geographical radius of the study centre and were chosen randomly based on the school register (organized in alphabetical order).…”
Section: Methodsmentioning
confidence: 99%
“…Asthma is one of the most common chronic diseases in childhood and is considered an important public health problem which leads to impairment of the quality of life (14,15) . Its main characteristic is inflammation of the airways, which leads to a condition of hyperreactivity to allergenic exposure and inhalation of irritants, or triggered by physical exercise (2) .…”
Section: Resultsmentioning
confidence: 99%
“…Asthma is a common chronic disease with 1 in 9 Australians diagnosed with the illness (AIHW, 2019). Globally, around 241 million people are living with asthma (Ellwood et al, 2017). Asthma is often treated with inhalational corticosteroids, which have been linked to increased rates of oral candidosis in those patients (Ellepola & Samaranayake, 2001; Kennedy et al, 2000).…”
Section: Discussionmentioning
confidence: 99%